2017
DOI: 10.1017/jfm.2017.515
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution of microscopic dewetting droplets with slip

Abstract: We investigate the dewetting of a droplet on a smooth horizontal solid surface for different slip lengths and equilibrium contact angles. Specifically, we solve for the axisymmetric Stokes flow using the boundary element method with (i) the Navier-slip boundary condition at the solid/liquid boundary and (ii) a time-independent equilibrium contact angle at the contact line. When decreasing the rescaled slip length $\tilde{b}$ with respect to the initial central height of the droplet, the typical non-sphericity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…First, in two articles McGraw et al implemented the boundary element method to gain insights into the internal flow fields of axisymmetric droplets. 29,30 They combined theory and experiment to study how droplets relax towards their new equilibrium shape on a substrate after an instantaneous change in the spatially uniform wettability. Second, Glasner 31 implemented the boundary element method to study the dynamics of droplets placed on substrates with static but non-uniform wettability profiles.…”
Section: Introductionmentioning
confidence: 99%
“…First, in two articles McGraw et al implemented the boundary element method to gain insights into the internal flow fields of axisymmetric droplets. 29,30 They combined theory and experiment to study how droplets relax towards their new equilibrium shape on a substrate after an instantaneous change in the spatially uniform wettability. Second, Glasner 31 implemented the boundary element method to study the dynamics of droplets placed on substrates with static but non-uniform wettability profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Thus there is sufficient time for the droplet to relax to a quasi-static shape when the apparent contact lines move. For the large slip length regime, elongational flow has been proposed to appear and dominate the viscous dissipation (Münch et al 2005), which has been observed for dewetting droplets (McGraw et al 2016;Chan et al 2017). The large slip regime in our model, assuming Poiseuille flow as the dominating flow structure, is considered as the intermediate slip regime in the analysis of Münch et al (2005).…”
Section: Camentioning
confidence: 67%
“…2016; Chan et al. 2017). The large slip regime in our model, assuming Poiseuille flow as the dominating flow structure, is considered as the intermediate slip regime in the analysis of Münch et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows that initially there exists a short transient while the rectangular film dewets into a thin liquid rivulet 25 . Following this a capillary rim is formed at short timescales and after coalescence of these rims a spherical cap droplet is formed at long timescales 4,26 . Due to the short length scale of the y-direction the dewetting and appearance of capillary rims is more prominent in the x-direction.…”
Section: Please Cite This Article As Doi: 101063/50010443mentioning
confidence: 99%